An economic assessment of soil carbon sequestration with biochar in Germany: Data documentation - Isabel Teichmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
[Introduction] This data documentation accompanies the study "An Economic Assessment of Soil Carbon Sequestration with Biochar in Germany" (Teichmann 2015), which analyzes the economically viable greenhouse-gas (GHG) mitigation potentials that can be obtained in Germany in 2015, 2030, and 2050 when slow-pyrolysis biochar is used for soil carbon sequestration and when the pyrolysis by-products - pyrolysis oils and gases - are turned into renewable energy. The analysis, which draws on the corresponding technical GHG mitigation potentials derived by Teichmann (2014a, b), focuses on the GHG mitigation costs of biochar produced from a wide variety of biomass residues diverted from conventional feedstock management. In addition to the detailed derivation of the net GHG mitigation costs of biochar entering Teichmann (2015), the data documentation gives background information on the total net avoided GHG emissions associated with biochar and presents any supplementary results tables referred to but not displayed in Teichmann (2015). The data documentation is organized as follows: Section S.2 provides the derivation of the net GHG mitigation costs of biochar - expressed per dry tonne of feedstock turned into biochar - used in Teichmann (2015) and gives some supplementary results tables. In turn, Section S.3 displays the biochar-related total net avoided GHG emissions per dry tonne of feedstock obtained from Teichmann (2014a, b), which serve to transform the net GHG mitigation costs per dry tonne of feedstock into net GHG mitigation costs per tonne of carbon-dioxide equivalent (CO2e) abated. Finally, Section A.4 presents supplementary results tables for the net GHG mitigation costs per tonne of CO2e abated.
Keywords: 330